Connecting dots of long COVID-19 pathogenesis: a vagus nerve- hypothalamic-pituitary- adrenal-mitochondrial axis dysfunction - Marta Camici; Giulia Del Duca; Anna Clelia Brita; Andrea Antinori (Frontiers in Cellular and Infection Microbiology)
The pathogenesis of long COVID (LC) still presents many areas of uncertainty. This leads to difficulties in finding an effective specific therapy. We hypothesize that the key to LC pathogenesis lies in the presence of chronic functional damage to the main anti-inflammatory mechanisms of our body: the three reflexes mediated by the vagus nerve, the hypothalamic-pituitary-adrenal (HPA) hormonal axis, and the mitochondrial redox status. We will illustrate that this neuro-endocrine-metabolic axis is closely interconnected and how the SARS-CoV-2 can damage it at all stages through direct, immune-inflammatory, epigenetic damage mechanisms, as well as through the reactivation of neurotropic viruses. According to our theory, the direct mitochondrial damage carried out by the virus, which replicates within these organelles, and the cellular oxidative imbalance, cannot be countered in patients who develop LC. This is because their anti-inflammatory mechanisms are inconsistent due to reduced vagal tone and direct damage to the endocrine glands of the HPA axis. We will illustrate how acetylcholine (ACh) and cortisol, with its cytoplasmatic and cellular receptors respectively, are fundamental players in the LC process. Both Ach and cortisol play multifaceted and synergistic roles in reducing inflammation. They achieve this by modulating the activity of innate and cell-mediated immunity, attenuating endothelial and platelet activation, and modulating mitochondrial function, which is crucial for cellular energy production and anti-inflammatory mechanisms. In our opinion, it is essential to study the sensitivity of the glucocorticoids receptor in people who develop LC and whether SARS-CoV-2 can cause long-term epigenetic variations in its expression and function.